DEVELOPMENT OF GENERAL COMPETENCE MASTER STUDENTS AS AN OBJECT OF SCIENTIFIC RESEARCH - Muromets, Viktoriya H. (Educological discourse, 2016)
The article is devoted to the theoretical analysis of the conceptual foundations of general competences of Master students in institutions of higher education. Naholoscheno that one of the main tasks of preparing students magistracy system is improving the quality of education on the basis of innovation; determination and regulation of content of all subsystems of education, ensuring the gradual development of the common (universal) competence, competitiveness in the external labor market, creating favorable conditions for professional development, development of leadership competencies.